IMPRESSING ONE PART OF THE CUT TOGETHER IN VIEW (British Journal of Global Ecology and Sustainable Development, 2022)
The article is unique in that the information is brief and clearly presented. To fully imagine the views. Learning how to properly perform part haircut and part look.